PERSAINGAN DUOPOLISTIK DINAMIS DENGAN HARGA LEKAT - , Reno Febrianty Ansorry, Dr. Salmah, M.Si. ([Yogyakarta] : Universitas Gadjah Mada, 2012)
This thesis discuss about duopolistic competition through time, with the assumption that the price of a homogeneous product does not adjust instantaneously to the price indicated by its demand function at the given level of output. The study start with the modeling of static Cournot. Then to get the optimal output solution we use partial differential equation method and matrix method for linear equation system. Hereafter we make the modeling of dynamic Cournot with sticky price. It is assumed that the evolution of the price through time is a function of the difference between the current price and the price on the demand function for each level of output. One of the main objective is to study the static Cournot equilibrium as an asymptotic limit of competition through time with sticky price as the speed of adjustment becomes instantaneous. The analysis is conducted under the assumptions that the demand is a linear function of price, the total cost is a quadratic function of output, and there is no uncertainty. This dynamic Cournot model is solved with an optimal control method. The optimal output solution is conducted from partial derivative from Hamiltonian function through state variable, costate variable and each players control.